Truly remote fiber optic sensor networks. (17th September 2019) - de Miguel Soto, Verónica; López-Amo, Manuel
Abstract: An overview of truly remote fiber optic sensors is presented in this work. It starts with a brief introduction of fiber optic sensor networks, showing their advantages and multiple applications. Then, the definition of truly remote networks is provided, and their main challenges discussed, such as increasing the sensing distance and the number of sensors interrogated. Several multiplexing techniques have been compared, such as wavelength, time and coherence division multiplexing. In relation to this, the most recent works showing multi wavelength fiber lasers for wavelength division multiplexing have been grouped and their versatility analyzed. Finally, recent and relevant truly remote fiber optic networks have been gathered and some of the most representative schemes explained in detail, comparing their multiplexing capability and the remoteness of the monitored sensors. Random distributed feedback fiber lasers form part of a number of these schemes, proving the suitability of this type of lasers for their use in ultra-long truly remote sensing applications.